Gold dinar acceptance in modern monetary system: empirical evidence in the context of gold dinar community in Malaysia / Ruzanifah Kosnin - Kosnin, Ruzanifah (2018)
The unstable and unjust fiat money system gave rise to the need to relook the role of gold as real money with stable values. Despite the advantage of gold (or gold dinar) as a stable and just medium in a monetary system, its implementation in the current system is challenging. Regardless of the challenges, effort in bringing a just monetary system has echoed in some countries and one of the most important elements to ensure the success of the implementation is the level of acceptance among the people. Therefore, the focus of this research is to investigate the comprehensive factors of gold dinar acceptance in order to understand gold dinar phenomenon in modern monetary system. The three main objectives of this research are as follows: (1) to identify factors contributing to the acceptance of gold dinar, (2) to provide an understanding of Islamic values in the practice of gold dinar and its role as money, and (3) to test and validate the Gold Dinar Acceptance Model (GDAM). A research-based model incorporating several theories of behavioural acceptance as well as emerging new factors known as perceived Islamic values and perceived knowledge was adopted to explain the relationships among various variables and to better understand the motivational factors underlying gold dinar acceptance. Exploratory studies using semi-structured interviews, observations and document analysis were employed to achieve the first two research objectives. Then 403 data collected using cross-sectional survey questionnaire from online gold dinar community in Malaysia to answer the third research question. Analysis using covariance-based Structural Equation Modeling (CB-SEM) technique revealed that perceived Islamic values, attitude, perceived knowledge, relative advantage and perceived behavioural control (facilitating condition) were significant factors in determining gold dinar acceptance, while trust, anxiety, subjective norms, and perceived behavioural control (self-efficacy) were insignificant factors. Of the basic TPB motivational factors (i.e., attitude, subjective norm, and perceived behavioural control), only attitude and perceived behavioural control (facilitating condition) influenced gold dinar acceptance. In addition, attitude fully mediated the relationship between perceived knowledge and relative advantage towards gold dinar acceptance. Overall, GDAM was sufficient in explaining gold dinar acceptance with 65.8 per cent variance. Therefore, this research provides support for the proposed GDAM in providing in-depth understanding of the relationships among various factors influencing gold dinar acceptance useful to the direction, development and implementation of gold dinar in the future. This research provides novel contribution in several ways. First, the development of measurement scale called Gold Dinar Acceptance Scale Measurement (GDASM) with sufficient validity and reliability. Secondly, the development and validation of GDAM provides comprehensive factors leading to gold dinar acceptance. Third, the establishment of new construct of perceived Islamic values provides us with deeper understanding of gold dinar phenomenon from Islamic behavioural perspectives. Finally, this research provides fundamental knowledge on gold dinar for the benefit of both academic and practitioners.